Assessment of Outcome of Hemorrhoidectomy in Adult Population - Amirishetty Bhaskar; B Srujan Kumar (Asian Journal of Medical Research, 2021)
Background: To assess outcome of hemorrhoidectomy in adult population. Subjects and Methods: One hundred five adult population with hemorrhoids of both genders were included and parameters such as symptoms, type of hemorrhoids and complications were recorded. Operating time (mins), first bowel movement (hours), return to normal daily activities (days) and VAS was also recorded. Results: Out of 105 patients, males were 60 (57.7%) and females were 55 (52.3%).  The mean operating time was 25.3 minutes, first bowel movement was 18.2 hours, return to normal daily activities was 6.7 days and VAS was 4.2. Common symptoms were pruritis in 68, mass through rectum in 32, bleeding through rectum in 14, soiling of clothes in 12 and pain during defecation in 40. Type of haemorrhoids was internal in 38, external in 38 and strangulated in 22 cases. The difference was significant (P< 0.05). Complications was bleeding seen in 1, urinary retention in 2 and both bleeding and urinary retention in 4 patients. The difference was significant (P< 0.05). Conclusion: Common symptoms were pruritis, mass through rectum, bleeding through rectum, soiling of clothes and pain during defecation. Complications were bleeding and urinary retention.